Financial Technology In Conditional cash Transfer dengan menggunakan Systematic Mapping Study - Rizkiansyah, Genta (Jurnal Ilmu Kesejahteraan Sosial, 2022)
This article is an initial study that seeks to explore the results of previous studies in the field of Financial Technology in the Conditional Cash Transfer Program using the Systematic Mapping Study (SMS). The purpose of this study is to determine the topic of Financial Technology in the Conditional Cash Transfer Program that has been studied. This study uses a qualitative method by using a literature study. The search was carried out in the Scopus database of 583 articles and after mapping, we found 25 articles with the publication year 2008-2020 that were published in scientific journals and entered the Scopus database and inclusion criteria. The results of this SMS can provide an overview of opportunities to explore new topics regarding Financial Technology in the Conditional Cash Transfer Program or take advantage of existing topics. The results of the Financial Technology study on the Conditional Cash Transfer Program with a focus on research on Credit Market, Electronic Payment, Financial Literacy, Financial Provision, Financial System, Microfinance and Social Investment. The locus of research is Household (Household), Community (Community), and Individual (Individual). The trend in the country of origin of publications that produces the most Financial Technology research in the Conditional Cash Transfer Program is in the Americas (56%) namely in the United States, Brazil, Mexico, and Uruguay. The next trend comes from Continental Europe (28%) namely from the United Kingdom, Italy, and France. Asia and Oceania (12%) came from Australia, Indonesia, and Saudi Arabia, lastly from Africa (4%) which only came from Tanzania.